Early remote ischaemic preconditioning leads to sustained improvement in allograft function after live donor kidney transplantation: long-term outcomes in the REnal Protection Against Ischaemia–Reperfusion in transplantation (REPAIR) randomised trial. (November 2019) - Veighey, Kristin V.; Nicholas, Jennifer M.; Clayton, Tim; Knight, Rosemary; Robertson, Steven; Dalton, Neil; Harber, Mark; Watson, Christopher J.E.; De Fijter, Johan W.; Loukogeorgakis, Stavros; MacAllister, Raymond
Abstract: Background: The REnal Protection Against Ischaemia–Reperfusion in transplantation (REPAIR) RCT examined whether remote ischaemic preconditioning (RIPC) improved renal function after living-donor kidney transplantation. The primary endpoint, glomerular filtration rate (GFR), quantified by iohexol at 12 months, suggested that RIPC may confer longer-term benefit. Here, we present yearly follow-up data of estimated GFR for up to 5 yr after transplantation. Methods: In this double-blind, factorial RCT, we enrolled 406 adult live donor kidney transplant donor–recipient pairs in 15 European transplant centres. RIPC was performed before induction of anaesthesia. RIPC consisted of four 5 min inflations of a BP cuff on the upper arm to 40 mm Hg above systolic BP separated by 5 min periods of cuff deflation. For sham RIPC, cuff inflation to 40 mm Hg was undertaken. Pairs were randomised to sham RIPC, early RIPC only (immediately pre-surgery), late RIPC only (24 h pre-surgery), or dual RIPC (early and late RIPC). The pre-specified secondary outcome of estimated GFR (eGFR) was calculated from serum creatinine measurements, using the Chronic Kidney Disease Epidemiology Collaboration equation. Predefined safety outcomes were mortality and graft loss. Results: There was a sustained improvement in eGFR after early RIPC, compared with control from 3 months to 5 yr (adjusted mean difference: 4.71 ml min −1 (1.73 m) −2 [95% confidence interval, CI: 1.54–7.89]; P =0.004). Mortality and graft loss were similar between groups (RIPC: 20/205 [9.8%] vs control 24/201 [11.9%]; hazard ratio: 0.79 [95% CI: 0.43–1.43]). Conclusions: RIPC safely improves long-term kidney function after living-donor renal transplantation when administered before induction of anaesthesia. Clinical trial registration: ISRCTN30083294.